Determinants of credit lending: empirical evidence from Indonesia with a sectoral and provincial approach - Argado, Carlos Emmanuel (2024)
Micro, Small, and Medium Enterprises or known as MSMEs have played an integral role in growth and development of the Indonesian economy. The contributions from businesses of these scales have provided significant merits in terms of Gross Domestic Product (GDP), employment manufacturing, and labour productivity which impact financial stability and economic resilience on a national scale. Despite its substantial roles to the country, MSMEs in Indonesia still face major constraints in obtaining credit and financing which have caused them to have such narrow limits in cultivating advancement and progress.